Consumer Perceived Risk by Online Purchasing: The Experiences in Hungary - Zita Balogh; Katalin Mészáros (Naše gospodarstvo/Our economy, 2020)
The aim of this paper is to identify and categorize the perceived risks that Hungarian consumers connect with online purchasing. The research is based on empirical data collected via a questionnaire and analysed with statistical software. The applied exploratory factor analysis identified five risk categories connected to online purchasing: perceived after-sale risk, perceived data security risk, perceived delivery risk, and perceived product risk. The fifth risk factor seems the most characteristic to Hungarian customers, who are wary of the possibility of online vendors selling fake products on the Internet. The results offer valuable information to companies engaged in online vending concerning the risk factors Hungarian consumers associate with online shopping. One limitation of this study is that it does not evaluate risk-reducing strategies.